Pengaruh Model Pembelajaran Matematic Realistic Terhadap Kemampuan Berfikir Kritis & Hasil Belajar Perkalian Di UPTD SDN Pangpong - Wahyuningsih, Sri Pertama; Wahyuningtyas, Sri; Hanifah, Sri Yuni (Jurnal Ilmiah Wahana Pendidikan, 2024)
Multiplication is material that students must master. These ingredients are essential ingredients that take quite a long time to grow. In fact, when it is presented in story problems, students often experience difficulties. Therefore, various efforts to improve the quality of lessons, especially mathematics subjects, continue to be carried out. These efforts include using appropriate media. The aim of the research was to determine the effect of realistic mathematical learning models on multiplication critical thinking abilities and students' multiplication learning outcomes at UPTD SDN Pangpong. This research used a quantitative approach, namely experimental research with a Quasi experimental design, using two classes with treatment, pre-test and post-test. The first conclusion is that there is a correlation between realistic mathematical learning models and critical thinking skills of 63.6% and significantly the variable correlation has a value of 0.015 and has an influence of 40.4% and significantly has a value of 0.010, secondly there is a correlation with learning outcomes. The correlation is 73.6% and the significance value is 0.033. then the influence that the realistic mathematical learning model has on learning outcomes has a percentage of 54.20% and a significant value of 0.028.